2018
DOI: 10.1097/wnr.0000000000000968
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic and microscopic diversity of missplicing in the central nervous system of patients with myotonic dystrophy type 1

Abstract: Myotonic dystrophy type I (DM1) is a multiorgan disease caused by CTG-repeat expansion in the DMPK gene. Sequestration of the splicing factor MBNL1 results in aberrant splicing in many genes in DM1 skeletal muscle, whereas MBNL2 plays a leading role in missplicing in the central nervous system (CNS) of patients with DM1. Splicing misregulation of most MBNL2-regulated genes occurs in the temporal cortex but not in the cerebellum of autopsied patients with DM1. To understand the diversity at macroscopic and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…We have previously examined the mis-splicing in DM1 patients for each area of the brain and found that mis-splicing in the cerebellum is less apparent than the other areas [3]. We also demonstrated the different degrees of mis-splicing that occurs among cell layers of the cerebellum [7]. These results clearly showed the heterogeneity of the brain and show that detailed splicing analysis for each cell or region is essential to clarify the pathomechanisms of this disorder.…”
Section: Introductionmentioning
confidence: 70%
“…We have previously examined the mis-splicing in DM1 patients for each area of the brain and found that mis-splicing in the cerebellum is less apparent than the other areas [3]. We also demonstrated the different degrees of mis-splicing that occurs among cell layers of the cerebellum [7]. These results clearly showed the heterogeneity of the brain and show that detailed splicing analysis for each cell or region is essential to clarify the pathomechanisms of this disorder.…”
Section: Introductionmentioning
confidence: 70%
“…We previously examined the mis-splicing in DM1 patients for each area of the brain and found that mis-splicing in the cerebellum is less apparent than in any other area [3]. We also demonstrated the different degrees of mis-splicing that occurs among cell layers of the cerebellum [7]. These results clearly showed the heterogenicity of the brain and show that detailed splicing analysis for each cell or region is essential to clarify the pathomechanisms of this disorder.…”
Section: Introductionmentioning
confidence: 82%
“…Using NCBI Primer-BLAST, we designed two sets of primers for each spliced gene; exon 4 forward and exon 6 reverse primers for exon 5 splicing, and exon 6 forward and exon 9 reverse primers for exons 7 and 8 splicing. In addition, we examined splicing patterns of other genes controlled by MBNL2: ADD1 exon 15, CACNA1D exon 11, CLASP2 exon 23a and 23b, CSCNK1D exon 9, KCNMA1 exon 27a, TANC2 exon 22a, GRIN1 exon 4, MAPT exon 2 and exon 12, using the primers used in our previous report [3, 7] (Tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…DM1-related aberrant splicing has been associated with the expression of fetal transcript variants (17,26,(44)(45)(46)(47). We performed a comprehensive evaluation of the developmental regulation of DM1related exon skipping events by comparing exon inclusion in frontal cortex samples from the human BrainSpan dataset (Figure 1A) and from a recent dataset including 21 DM1 patients and 8 controls (Figure 1B) (23,31).…”
Section: Splicing Patterns In the Frontal Cortex Of Adult Dm1 Patients Resemble Those Of Developing Brainsmentioning
confidence: 99%